1990
DOI: 10.1164/ajrccm/142.6_pt_1.1258
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Plasma Platelet Activating Factor in Persistent Pulmonary Hypertension of the Newborn

Abstract: Platelet activating factor (PAF) is an endogenous phospholipid mediator that causes pulmonary hypertension and thrombocytopenia in experimental animal models. To investigate circulating PAF in persistent pulmonary hypertension of the newborn (PPHN), we studied PAF and its degradative enzyme, acetylhydrolase. Thirteen neonates with PPHN, diagnosed by routine clinical methods including echocardiography, were compared to six age-matched control patients with respiratory distress. Overall, plasma PAF levels were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
30
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 14 publications
2
30
0
Order By: Relevance
“…The level of plasma PAFacetylhydrolase activity also can be altered by acquired factors. Changes in the activity of plasma acetylhydrolase have been found in conjunction with asthma (38,45), systemic lupus erythematosus (46), hypertension (47,48), chronic cholestasis (49), and necrotizing entercolitis (50,51). In the case of clinical sepsis, two conflicting reports have been published.…”
Section: Discussionmentioning
confidence: 99%
“…The level of plasma PAFacetylhydrolase activity also can be altered by acquired factors. Changes in the activity of plasma acetylhydrolase have been found in conjunction with asthma (38,45), systemic lupus erythematosus (46), hypertension (47,48), chronic cholestasis (49), and necrotizing entercolitis (50,51). In the case of clinical sepsis, two conflicting reports have been published.…”
Section: Discussionmentioning
confidence: 99%
“…Neonates with PPHN have high PAF levels (Caplan et al, 1990), showing that persistence of high PAF levels postnatally leads to abnormal perinatal pulmonary adaptation. We speculate that inhibition of PKG and PKA activities by high PAF levels and the inability of cyclic nucleotides to downregulate PAFr-mediated effects postnatally will also contribute to development of PPHN.…”
Section: Paf and Regulation Of Pkg And Pka Activities In Perinatal Pumentioning
confidence: 99%
“…We recently showed that acute hypoxia up-regulates PAFr-mediated intracellular signaling in ovine fetal pulmonary vascular smooth muscle (Ibe et al, 2005). Therefore, chronic hypoxia in the perinatal period may result in abnormal up-regulation of PAFr protein expression, PAFr binding, and PAFr-mediated cell signaling, leading to increased pulmonary vasomotor tone and vascular remodeling, a key event in the onset of clinical disorders such as persistent pulmonary hypertension of the newborn (PPHN) (Caplan et al, 1990).…”
mentioning
confidence: 99%
“…Additionally, IFN-␥ and LPS decreased the human PAF acetylhydrolase promoter activity by 35% and 50% respectively in monocyte-derived macrophages and various established macrophage cell lines (11). However, changes in the in vivo activity of plasma PAF acetylhydrolase have been documented in conjunction with asthma (12), systemic lupus erythematosus (13), hypertension (14,15), chronic cholestasis (9), and necrotizing enterocolitis (16,17). In most cases, the levels of circulating PAF acetylhydrolase activity are increased as a physiological response to inflammatory stimuli.…”
mentioning
confidence: 99%